Judicial-Legal Consideration of Transaction Extant Human Frozen Gametes in Cryopreservation Banks - Mahmoodian, Nazli; Abbasi, Mahmoud (Bioethics and Health Law Journal (BHL), 2026)
Gametes (Sperm & ovule) cryopreservation method is one of the resent subjects in medical fertility that helps child bearing in the future The cryopreservation-anybody that cannot bearing child nonce-with the purpose of bearing genetic children in the future, have been frozen their gametes and store them in gamete cryopreservation banks, but in some cases because of changing their opinion about having child or curing their disease and being able to nature procreation the applicants don’t need their frozen gametes nevermore. So, some of them tend selling them. But because of descent affiliation and its Judicial-Legal effects there is a big challenge between the opponents and consents about their transaction. On the other hand todays, human gametes trading is one of the most important problems, so it seems considering this topic is essential, but unfortunately there is not any academic research in this field in Iran. So, in this project we hardly tried to find the best Judicial-Legal solutions the problems in this field, because this is an applied and theoretical research in the theology field, there is no material. The main method in this research is bookcase. According to jurisprudence opinions based on the gametes’ impurity the human gamete transaction had been prohibited in the past, but attentions show that it refers to their usage at that time not their impurity so this prohibition cannot be entirely. Todays, because of their different medical, pharmacist, fertility, etc... usages they can be considered as property and there isn’t any prohibition for their transaction because of impurity. However, there isn’t any Judicial-Legal problems for transaction human frozen gametes which are extant in cryopreservation banks but, for the legal prohibition of donation medical fertility and marriage cancelling in bearing child at single status their transaction for the purpose of fertility is forbidden. But in some case such as medical, pharmacist, fertility, etc... researches according to the ethical codes it is permitted.